Navigating pathways to develop self-compassion in sport, dance, and music: Qualitative insights from volunteer participants on balancing criticism and compassion, the pivotal influence of the social environment and strategies to overcome setbacks - Céline Kosirnik; Roberta Antonini Philippe; Valentino Pomini (PLoS ONE, 2025)
Self-compassion has emerged as a valuable skill for performers, contributing to both their well-being and performance enhancement. However, the question remains: how can it be effectively integrated and cultivated within performers’ daily practice? This study examines the extent to which self-compassion is integrated by performers, its practical application, and the role of the social environment in shaping these skills. A total of 27 performers (athletes, dancers, and musicians), aged 14–27, practicing at a pre-professional level, participated in semi-structured interviews. These interviews explored performers’ responses to challenging situations during practice, the coping strategies employed, the use or non-use of self-compassion, and the influence of their social environment. Through a thematic analysis, six key themes emerged, each comprising subthemes: Explore your inner critic; Balance over-identification; Use strategies to overcome setbacks; Create a virtuous circle; Acknowledge your social environment; and, Learn about yourself. The findings revealed that performers continue to place significant emphasis on self-criticism, often neglecting self-kindness when most needed. Despite this, they recognize the benefits of self-compassion and report various strategies to manage difficulties. Additionally, the importance of the coach’s communication style and the performers’ desire to be better understood by their coach were emphasized. This qualitative study provides deeper insights into the experiences of performers and offers practical guidance on how self-compassion can be more effectively integrated into their daily practice.